2014
DOI: 10.1111/chd.12192
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Tracheostomy Following Congenital Heart Surgery: A Contemporary Experience

Abstract: The timing of tracheostomy placement may be an important factor in clinical outcomes for pediatric patients with persistent dependence on mechanical ventilatory support following congenital heart surgery. A larger, multi-institution study may help further elucidate our observed clinical findings in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…Despite a low rate of tracheostomy procedures in children following congenital heart surgery (1.2%–2.7%), history of prior cardiac surgery has been identified as an independent risk factor for mortality in infants within 1 year after tracheostomy . Although children with congenital heart disease have a higher mortality rate following tracheostomy than children without, they rarely die during the index hospitalization; in‐hospital mortality is equivalent to that of children without congenital heart disease . Further investigation of these associations is warranted because there is a nationwide trend toward performing more tracheostomies in children with congenital heart disease …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a low rate of tracheostomy procedures in children following congenital heart surgery (1.2%–2.7%), history of prior cardiac surgery has been identified as an independent risk factor for mortality in infants within 1 year after tracheostomy . Although children with congenital heart disease have a higher mortality rate following tracheostomy than children without, they rarely die during the index hospitalization; in‐hospital mortality is equivalent to that of children without congenital heart disease . Further investigation of these associations is warranted because there is a nationwide trend toward performing more tracheostomies in children with congenital heart disease …”
Section: Introductionmentioning
confidence: 99%
“…The current literature suggests that there may be independent risk factors for mortality following pediatric tracheostomy . Further characterization of these risks may be difficult to capture through national inpatient databases that can be limited by coding error bias and inability to follow individual patients longitudinally.…”
Section: Introductionmentioning
confidence: 99%
“…Single-institution studies (Challapudi, Natarajan & Aggarwal;LoTempio & Shapiro;Hoskote et al, 2005;Rossi et al, 2009;Cotts et al, 2011;Costello et al, 2014) have reported indications and outcomes of tracheostomy in this population, but these studies have been small (sample size range: 4-59) and lack external validity because of substantial heterogeneity in institutional practices surrounding postoperative ventilator management and decision-making about tracheostomy. These studies report different patterns of how commonly tracheostomy is used in this population and the timing of its performance.…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10][11][12] However, most studies have focused on the indications for tracheostomy, the subsequent outcomes, or resource utilization. 6,[10][11][12][13][14][15][16][17][18][19][20][21][22] Data are scant regarding the epidemiological risk factors for tracheostomy in CHD, and there have been no large-scale population-based studies. Furthermore, among infants with CHD requiring a tracheostomy, previous studies have failed to investigate either the overall mortality risk or the mortality risk stratified by a follow-up period.…”
Section: Introductionmentioning
confidence: 99%